Selection, Identification, and Application of Aptamers against Agaricus bisporus Lectin to Establish an Aptamer-AuNPs Colorimetric Method for Detection of ABL. (22nd October 2020) - Gao, Hao; Tian, Yiling; Zhang, Min; Liu, Jianhui; Yuan, Yaowu; Tan, Jianxin; Ma, Aijin
Abstract : Agaricus bisporus lectin (ABL), which is one of the antinutritional factors in A . bisporus, is an important allergen and harmful to human health. Due to the shortcomings of the current detection methods, it is extremely urgent to establish a rapid and sensitive detection method for ABL in foods. To isolate the ssDNA aptamer of ABL, 13 rounds of subtractive systematic evolution of ligands by exponential enrichment (SELEX) selection were carried out. As a result, six candidate aptamers were selected and further examined for their binding affinity and specificity by enzyme-linked aptamer method. One aptamer (seq-41) against ABL with a high affinity and specificity was isolated and demonstrated to be the optimal aptamer whose dissociation constant reaches the nanomolar level, Kd = 31.17 ± 0.1070 nM. Based on seq-41, an aptamer-AuNPs colorimetric method was established to detect ABL with a linear range of 0.08∼1.70 μ g/mL and the detection limit is 0.062 μ g/mL. This study provides a novel aptamer-AuNPs colorimetric method with high sensitivity and specificity for detection of ABL and a novel strategy for development of detection method of fungal or plant allergens.